Efficacy of pulsed short wave therapy in symptomatic TMD patients: Randomized control trial - Sadhurya M Dhanasekaran; A Kannan; Krithika C Lakshmi; G Anuradha; K Yesoda Aniyan (Wolters Kluwer Medknow Publications, 2022)
Context: Temporomandibular joint (TMJ) is a ginglymoarthroidal joint of synovial variety. The joint's pathology includes those predominantly of musculoskeletal origin, which poses a complex problem in the clinical scenario. The management of temporomandibular joint disorders (TMD) remains a challenge due to the intricate anatomy of the joint and the multipart etiologies associated with it. Aims: This study aimed to compare the effectiveness of pulsed short wave therapy (PSWT) with pharmacotherapy in symptomatic TMD patients. Methods and Material: A total of 62 patients were included in this randomized control trial and were randomly allotted into two groups. Patients in Group I received PSWTand Group II received a combination of a muscle relaxant and a nonsteroidal anti-inflammatory drug (NSAID) for 5 consecutive days. Visual analog scale (VAS) scores were recorded during the follow-up. Statistical Analysis Used: The statistical analysis was performed using Stata/SE 17.0 statistical software. Results: There was a statistically significant difference in the groups for different periods. Kaplan-Meier function and extended survivor function tests showed better pain alleviation in the short wave therapy group. Conclusion: The current study shows that PSWT decreased pain without adverse effects. Therefore, it could be considered a safe and potentially effective adjuvant therapeutic modality for TMD.